2018
DOI: 10.3390/molecules23123328
|View full text |Cite
|
Sign up to set email alerts
|

Tetra-glucopyranosyl Diterpene ent-Kaur-16-en-19-oic Acid and ent-13(S)-Hydroxyatisenoic Acid Derivatives from a Commercial Extract of Stevia rebaudiana (Bertoni) Bertoni

Abstract: Stevia rebaudiana and its diterpene glycosides are one of the main focuses of food companies interested in developing novel zero calorie sugar substitutes since the recognition of steviol glycosides as Generally Recognized as Safe (GRAS) by the United States Food and Drug Administration. Rebaudioside A, one of the major steviol glycosides of the leaves is more than 200 times sweeter than sucrose. However, its lingering aftertaste makes it less attractive as a table-top sweetener, despite its human health benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“… (a) NMR spectra recorded in Pyr- d 5 , (b) MeOH- d 4 . 14 : rebaudioside Y (X = 6) [ 58 ]; 15 : rebaudioside A ( * Glc, X = 3) [ 79 ] 16 : rebaudioside Z ( * Glc, X = 6) [ 31 ]; 17 : 13-[(2-O-β-D-glucopyranosyl-3-O-β-D-glucopyranosyl-β-D-glucopyranosyl) oxy]ent-hydroxyatis-16-en-19-oic acid -β-D-glucopyranosy ester ( * Glc, X = 3) [ 31 ]; 18 : 13-[(2- O -(6- O -β-D-glucopyranosyl)-3-O-β-D-glucopyranosyl-β-D-glucopyranosyl)oxy] kaur-16-en-18-oic acid β-D-glucopyranosyl ester ( * Glc, X = 6 as follows Glcβ(1-6)Glcβ(1-2)Glcβ 1 - [ 65 ]; 19 : 13-[(2- O -β-D-glucopyranosyl-3- O -β-D-fructofuranosyl-β-D-glucopyranosyl)oxy] kaur-16-en-18-oic acid β-D-glucopyranosyl ester ( * Fru, X = 3) [ 65 ]. NA: not assigned.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… (a) NMR spectra recorded in Pyr- d 5 , (b) MeOH- d 4 . 14 : rebaudioside Y (X = 6) [ 58 ]; 15 : rebaudioside A ( * Glc, X = 3) [ 79 ] 16 : rebaudioside Z ( * Glc, X = 6) [ 31 ]; 17 : 13-[(2-O-β-D-glucopyranosyl-3-O-β-D-glucopyranosyl-β-D-glucopyranosyl) oxy]ent-hydroxyatis-16-en-19-oic acid -β-D-glucopyranosy ester ( * Glc, X = 3) [ 31 ]; 18 : 13-[(2- O -(6- O -β-D-glucopyranosyl)-3-O-β-D-glucopyranosyl-β-D-glucopyranosyl)oxy] kaur-16-en-18-oic acid β-D-glucopyranosyl ester ( * Glc, X = 6 as follows Glcβ(1-6)Glcβ(1-2)Glcβ 1 - [ 65 ]; 19 : 13-[(2- O -β-D-glucopyranosyl-3- O -β-D-fructofuranosyl-β-D-glucopyranosyl)oxy] kaur-16-en-18-oic acid β-D-glucopyranosyl ester ( * Fru, X = 3) [ 65 ]. NA: not assigned.…”
Section: Figurementioning
confidence: 99%
“…All these developments have allowed the discovery of several new natural and slightly modified DGs with remarkable potential as sugar substitutes e.g., several rebaudioside A isomers, a stevioside like-compound with a disaccharide linked at position C-12 of the aglycone [ 22 ], rebaudioside R (unique example with a non-glucose monosaccharide linked directly at position C-13 (xylose) [ 23 ], rebaudioside U and similar compounds, the only steviol glycosides with an arabinopyranosyl moiety [ 24 , 25 ], rebaudioside W (unique hexa-glycoside from S. rebaudiana with three different sugar monosaccharides attached (glucose, xylose and rhamnose) [ 26 ]. Additionally, rebaudioside IX series are the largest natural DGs composed of nine glucose units linked to steviol [ 27 , 28 , 29 ], only one natural example of rebaudioside M isomer has been reported [ 30 ] and a few new compounds with an ent -atisene core have also been reported [ 31 , 32 ]. Nowadays, many natural, chemically, and enzymatically modified diterpene glycosides with diverse sugar interlinkages and cores have been discovered, hence, a wide spectrum of structures are now available to evaluate for their sweetener potential and to understand better the relationship between structure-sweetness/lingering aftertaste.…”
Section: Introductionmentioning
confidence: 99%
“…The sugar compositions of the new glycosides were estimated; however, the position and the stereochemistry of the attached sugars could not be determined by MS analysis. In addition, the possibility of the presence of 6-deoxy-Glc instead of Rha or aglycon isomer could not be excluded since they have been detected in stevia extract. Therefore, the putative steviol glycosides (Figure ) were synthesized to confirm their structures and conduct sensory evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the possibility of the presence of 6-deoxy-Glc instead of Rha 21 or aglycon isomer 22 could not be excluded since they have been detected in stevia extract. Therefore, the putative steviol glycosides (Figure 2) were synthesized to confirm their structures and conduct sensory evaluations.…”
Section: Chemical Syntheses Of Newly Identified Steviol Glycosides Th...mentioning
confidence: 99%
“…The presence of this class of chemistry in S. rebaudiana was recently reported. 5 Extensive analysis of 1D and 2D NMR data, including that based on 1 H, 13 C, 1D-TOCSY, 1 H-1 H COSY, 1 H-13 C HSQC-DEPT, 1 H-13 C HMBC, and 1 H-1 H ROESY experiments, confirmed that 1 to 5 contained the ent-atisene core with a varying number of sugar units attached to that core (see Supporting Information for representative 1D and 2D NMR spectra). The complete 1 H and 13 C NMR assignments of compounds 1 to 5 are provided in Tables 1 and 2, respectively.…”
mentioning
confidence: 99%